(untitled) (Research, Society and Development, 2023)
Primary health care (APS) is the communication center of health care networks and its function is to coordinate care. The objective of this work was to analyze the oral health care network for people with disabilities (RASB-PcD) and to identify the main challenges and potentialities so that APS can fulfill its coordinating role. This is a qualitative, exploratory-descriptive research. Data collection through focus groups and interviews with oral health professionals who work in micro-regions of Minas Gerais. The technique for data analysis was Laurence Bardin’s content analysis, with the help of the IRAMUTEQ software. The referral flow in this RASB-PcD is established, but it has inconsistencies, whereas the counter-referral flow shows weaknesses. Criteria and protocols for access to hospital services need to be better discussed and preoperative tests need to be performed in a timely manner. The offer of vacancies in specialized services and in hospital services was identified as a challenge. Improving communication and articulation between professionals, through solid strategies of matrixial support and permanent education, emerged as a potential so that APS can coordinate care and guarantee its longitudinality, providing comprehensive care for people with disabilities.